2023
DOI: 10.1186/s12905-023-02498-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and associated factor towards cervical cancer prevention among primary and secondary school female teachers in Gondar town, North West Ethiopia, 2022

Birtukan Atena Negash,
Netsanet Habtie Bayu,
Ashenafi Worku Woretaw

Abstract: Introduction Cervical cancer is uncontrolled proliferation of cells on the cervix. Worldwide, millions of women suffer from this disease. Cervical cancer can be prevented by increasing awareness and changing negative attitude about the cause and prevention of cervical cancer. The aim of this study was to identify the gap of knowledge, attitude and associated factor about cervical cancer prevention. Method Institution-based cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…The results of this study showed that only 28 % of women knew about CC screening. This is in contrast to previous studies conducted in different parts of Ethiopia 38.4 % [ 28 ], 48.4 % [ 29 ], 49.5 % [ 30 ], and 50.7 % [ 21 ]. This difference may be due to the number of observations, the study area, the variables included in the study, and statistical modeling.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The results of this study showed that only 28 % of women knew about CC screening. This is in contrast to previous studies conducted in different parts of Ethiopia 38.4 % [ 28 ], 48.4 % [ 29 ], 49.5 % [ 30 ], and 50.7 % [ 21 ]. This difference may be due to the number of observations, the study area, the variables included in the study, and statistical modeling.…”
Section: Discussioncontrasting
confidence: 98%
“…The study also showed that 57 % of the participants had a positive attitude towards screening. It has previously been shown that women are better able to make an informed decision about screening when they are fully informed and have a positive outlook on the dangers of cervical cancer and how to prevent it [ 12 , 21 , [28] , [29] , [30] , 32 ]. The result of this study is better than the study conducted in Ethiopia 46.1 % [ 21 ] and in Zambia 36.5 % [ 12 ].…”
Section: Discussionmentioning
confidence: 99%